Decision analysis - Clemen, Robert (Henry Stewart Talks, 2011)
Why decision analysis?, Sources of difficulty, Intuitive versus deliberative thinking, Decision analysis framework, Elements of decisions, Jack Rabbit Racing example, Decision analysis tools, Decision trees, MANPADS example, Subjective judgments, Preferences and trade-offs, Expert probability judgments, Nuclear waste repository example, Monte Carlo simulation, Space shuttle heat tile example, SS Central America example, Value of decision analysis, Decision analysis in organizations, SmithKline Beecham example, Summary and conclusion
Reviewed at 2018/06/27